2004
DOI: 10.1111/j.1936-4490.2004.tb00322.x
|View full text |Cite
|
Sign up to set email alerts
|

A Global Mindset — A Prerequisite for Successful Internationalization?

Abstract: AbstmctThis study offers a contribution to our understanding of the role of a global mindset in the successful internationalization of small and medium-sized companies. The particular focus is on the drivers of the global mindset and the connection with performance. We created a framework and tested it, empirically, with a representative sample of small Finnish companies in the field of information and communications technology (ICT). The jndings indicate that managerial experience and market characteristics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
328
2
17

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 349 publications
(361 citation statements)
references
References 36 publications
14
328
2
17
Order By: Relevance
“…The inclusion of three kinds of mindsets (ethnocentric, polycentric, and geocentric) as moderator between antecedents and export performance provide a more robust explanation for variations in export performance. These results also support the conclusion by Nummela et al (2004) that managerial experience and market characteristics are important drivers of the global mindset, which, in turn, is one of the key parameters of international performance. As opined by many CEOs, developing a company global mindset is a "prerequisite for global industry dominance."…”
Section: Discussion and Managerial Implicationssupporting
confidence: 78%
See 1 more Smart Citation
“…The inclusion of three kinds of mindsets (ethnocentric, polycentric, and geocentric) as moderator between antecedents and export performance provide a more robust explanation for variations in export performance. These results also support the conclusion by Nummela et al (2004) that managerial experience and market characteristics are important drivers of the global mindset, which, in turn, is one of the key parameters of international performance. As opined by many CEOs, developing a company global mindset is a "prerequisite for global industry dominance."…”
Section: Discussion and Managerial Implicationssupporting
confidence: 78%
“…Arora et al (2004) concluded that training in international management, manager's age, foreign country living experience, family member from a foreign country, and job experience in a foreign country have statistically significant impacts on managers' global mindset, and argue that global mindset is a trait that can be developed with training. Nummela, Saarenketo, and Puumalainen (2004) concluded that market characteristics-globalness of the market in which the firm operates and the turbulence of the market-are positively related to global mindset. Furthermore, the authors found a positive relationship between "global mindset" and financial indicators of the firm's international performance.…”
Section: Export Mindsetmentioning
confidence: 99%
“…This is in line with Nummela et al (2002) and her view on the importance of the manager's mindset for an international performance. According to Spence (2003), high-tech SMEs follow a planned international strategy.…”
Section: The Entrepreneur's Visionsupporting
confidence: 68%
“…His strategy will then give the important guidelines for the organisation, but changes can still be made. The importance of this has also been shown by Nummela et al (2002) who state that a manager's global mindset is important for international performance. Mental thinking forms an entrepreneur's visions and is a base for selecting different strategies.…”
Section: Introductionmentioning
confidence: 93%
“…As Ocasio (1997: 197) notes, "The most critical players in attention regulation are typically the CEO and the top management group," and a long line of research has shown that executives' backgrounds drive the decisions they make (Hambrick & Mason, 1984;Waldman, Siegel, & Javidan, 2006b;Hambrick, 2007). Furthermore, CEOs' personal attitudes and values have been shown to be a key driver of CSR (Hemingway & Maclagan, 2004), and international experience helps shape the global mindset of the CEO (Carpenter, Sanders, & Gregersen, 2001;Nummela et al, 2004). Such international experience and global mindset may lead to a greater focus on global issues and diversity (Carpenter & Fredrickson, 2001), and make the CEO more open to the adoption of international diversified standards of CSR.…”
Section: H3mentioning
confidence: 99%